Picolinic Acid, a Catabolite of Tryptophan, Has an Anabolic Effect on Bone In Vivo. (17th August 2020) - Duque, Gustavo; Vidal, Christopher; Li, Wei; Al Saedi, Ahmed; Khalil, Mamdouh; Lim, Chai K; Myers, Damian E; Guillemin, Gilles J
ABSTRACT: Fractures attributable to osteoporosis have a severe impact on our older population. Reports of side effects with commonly prescribed osteoporosis drugs have led to the investigation of new and safer treatments with novel mechanisms of action. Picolinic acid (PIC), a catabolite of tryptophan, induces in vitro osteogenic differentiation of mesenchymal stem cells. Here we demonstrate that PIC has an anabolic effect on bone in vivo by increasing bone formation, bone mass, and bone strength in normal and ovariectomized C57BL/6 mice. Activation of the osteogenic pathways triggered this osteoanabolic response without any cross‐related effects on mineral absorption or calciotropic hormones. Because PIC was also well tolerated and absorbed with no side effects, it is an ideal potential candidate for the treatment of osteoporosis. © 2020 American Society for Bone and Mineral Research.